Eyetracking a meeting of minds: teachers’ and students’ joint attention during synchronous online language tutorials - Shi Lijing; Stickler Ursula (Journal of China Computer-Assisted Language Learning)
The COVID-19 pandemic forced many language teachers to move their teaching online without sufficient preparation. This unexpected change of practice engendered doubt and anxiety in teachers. They worried about their ability to attract and hold their learners’ attention, an element that is essential for successful online teaching. Our dual-point eyetracking study looks into how students and teachers establish joint attention during online language tutorials. It also examines various means teachers employ to guide students’ attention and scaffold their meaning making process. The data was collected from two online language tutorials where the eye movement of one teacher and one student was tracked simultaneously, as well as recordings of their stimulated reflection while watching their own eyetracking visualisation replay. By combining mixed-method data and dual perspectives, we were able to unveil the complex interactions in online language tutorials and offer practical suggestions to language practitioners who hope to improve their online teaching skills.